A study on rheological properties of various gelling agents for topical applications - Abdul Rahman, Mohammad Nasrin; Abdul Qader, Omar Abdul Jabbar; Sukmasari, Susi; Ibrahim, Mohammad; Ismail, Ahmad Faisal; Doolaanea, Abd Almonem (2016)
A sum of 26 gels were prepared, each with different materials of gelling agent. All 26 gelling agent materials was prepared with the same concentration of 3% w/w, and added with 5% w/w propylene glycol as solubilizer, 0.1% w/w methyl paraben, and 0.03%w/w propyl paraben as preservatives. A standard 3% gel concentration was prepared for each of the gelling agents, and all other procedure was kept constant. The gels were then analysed using Rheometer to compare their rheological properties. There are 3 screening phase where initially, each of the gels were analysed using creep test to study their Shear stress, shear rates, and viscosity profiles. If they show an acceptable pseudoplastic material, stress sweep test were then conducted to study the stability of the gels in a range of stress applied. If that particular gel has linear viscoelastic region, frequency sweep test is conducted to confirm its stability profiles. There are 15 gels having good pseudoplastic rheology properties. These15 gelling agents were tested with stress sweep and frequency sweep test. Lastly, only 3 gels were screened to have stable linear viscoelastic range with stress and frequency sweep test. All the rheological properties were well documented for each of the gelling agents.